Presidents and their justices - Clouatre, Douglas (The Rowman & Littlefield Publishing Group, 2010)
Presidents and their Justices offers an innovative look at the relationship between a president and the Supreme Court justices they appoint. Based on a 2005 survey of historians, lawyers, and political scientists that ranked presidents according to their Supreme Court appointments, the ratings offer a distinctive analysis of the relationship between presidents and the justices they appointed. Among these were Herbert Hoover, as the fifth-ranked president based on the Court nominees and Harry Truman, as one of the worst twentieth-century presidents for the justices he appointed. The book delves into presidential Court appointments and how a justice's career affects a president's legacy. Among the presidents studied are Warren Harding, Ulysses Grant, John Kennedy, Ronald Reagan, and Franklin Roosevelt. The work is divided into sections of great presidents who made successful appointments, great presidents who failed in their appointments, and mediocre presidents who made successful appointments.